Clinical and Pathological Research on Myositis - Akinori Uruha (Neurology and Clinical Neuroscience, 2026)
ABSTRACT Idiopathic inflammatory myopathy, or autoimmune myositis, has traditionally been classified as polymyositis and dermatomyositis; however, advances in serological and pathological analyses have revealed the limitations of this framework. Currently, the major subtypes of autoimmune myositis include dermatomyositis, antisynthetase syndrome, immune‐mediated necrotizing myopathy, and inclusion body myositis. This review summarizes recent advances in understanding the clinical and pathological features and pathomechanisms of each autoimmune myositis subtype, which serve as the basis for modern classification. We identified the expression of myxovirus resistance protein A, a Type I interferon‐induced protein, in the sarcoplasm as a novel pathological marker of dermatomyositis, improving diagnostic sensitivity. Although some symptoms overlap between dermatomyositis and antisynthetase syndrome, these two conditions are distinct in their pathological characteristics. Antisynthetase syndrome‐associated myositis is characterized pathologically by perifascicular necrosis, in contrast to the perifascicular atrophy seen in dermatomyositis. Moreover, an immunological micro‐milieu favorable to plasma cell survival is specifically present in the skeletal muscle of antisynthetase syndrome. Immune‐mediated necrotizing myopathy is pathologically defined by a prominent necrotic and regenerating process. Importantly, some pediatric and young adult cases resemble muscular dystrophy, potentially leading to delays in diagnosis and treatment. High serum creatine kinase levels exceeding 1000 U/L, a clinical diagnosis of “muscular dystrophy” without genetic confirmation, and onset during normal motor development are red flags for this disease. Inclusion body myositis is characterized by both inflammatory and degenerative features and may represent a disease spectrum that includes an earlier stage, polymyositis with mitochondrial pathology.